Horizontal versus vertical interdependence in multinational activity - Harald Badinger; Peter Egger (Center for Economic Studies and ifo Institute (CESifo), 2008)
Recent research in international economics highlights the role of interdependencies of investment decisions and sales of multinational firms. Previous work focused on and provided evidence for aggregate flows or stocks of foreign direct investment, showing that interdependence declines in geographical distance among host countries. This could be interpreted as implicit evidence for export-platform foreign direct investmentan activity which creates a complementary relationship between (potential) host markets through final goods exports of foreign subsidiaries to third countries. This paper sheds light on interdependencies that are brought about by (horizontal) trade in final goods and (vertical) trade in intermediate goods (within and between host countries). For this, we use a panel data set of U.S. foreign affiliate sales to 16 developed countries in 7 industries over the period 1983-2000. As one of the first studies on that matter, we explicitly distinguish between horizontal and vertical interdependence in MNE activity and allow for both market size (demand) related as well as remainder linkage effects. The latter are captured by a second order spatial regressive error process. Overall, there is evidence for mainly vertical as opposed to horizontal interdependence and, hence, mainly vertical motives of multinational activity.
Keywords: C21; C23; F21; F23; 330; multinational firms; foreign affiliate sales; spatial econometrics; generalized method of moments estimation; panel data analysis; Multinationales Unternehmen; Auslandsniederlassung; Umsatz; Direktinvestition; Amerikanisch; Lieferanten-Kunden-Beziehung; Panel; USA; Welt